Quantitative asymptotic regularity results for the composition of two mappings. (3rd August 2017) - Kohlenbach, Ulrich; López-Acedo, Genaro; Nicolae, Adriana
Abstract : In this paper, we use techniques which originate from proof mining to give rates of asymptotic regularity and metastability for a sequence associated to the composition of two firmly nonexpansive mappings.